The impact of debt financing on the value of a company: The case of North Macedonian companies - Andrijana Bojadzievska Danevska; Elena Parnardzieva Stanoevska; Savica Dimitrieska (Naše gospodarstvo / Our Economy, 2023)
The purpose of this paper is to determine the relation between a company's indebtedness and its value. We used a sample of 20 North Macedonian companies, listed on the Macedonian Stock Exchange (MSE) mandatory listing, and the data for 6 years' time span. In the paper, we use Panel Data models (Pooled OLS regression, Fixed and Random Effects models) to estimate the relation between debt financing and the company's value measured by return on assets (ROA) and Tobin's Q. According to the results of short-term debt has a statistically significant and negative impact, while the return on investments in human capital (HCROI), company's size and current ratio have a positive and statistically significant impact on the ROA. When investigating the impact of indebtedness on a company's value measured by Tobin's Q, short-term and long-term debt have positive and statistically significant effects. Our research suggests that while debt increases a company's indicators for market performance, it also decreases the company's accounting operating performance. Therefore, when analyzing a company's value, investors should be considering not only Tobin's Q, which can be sometimes regarded as a market-to-book value ratio, but also to look at the fundamental ratios, such as ROA, ROE (return on equity) and EPS (earnings per share).
Keywords: G32; C33; 330; Company's value; Short-term debt; Long-term debt; Financial leverage; North Macedonia